Direct Torque Control: Stator Flux Regulation Improvement at Low Speed - Nik Rumzi Nik Idris (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
A simple method to improve stator flux regulation of a direct torque control (DTC) of induction motor drive is presented. By using this method, the simple control structure of DTC is retained and no modification to the voltage vectors look-up table is required. To implement this technique, the index to the look-up table is modified so that the reverse voltage vectors are selected (instead of zero-voltage vectors) whenever the stator flux regulation fails. To study the viability and the effectiveness of this simple method in improving the flux regulation at low speed, experiments are conducted to a ¼ hp induction motor with DTC technique. The control algorithm is implemented using a DS1104 controller board with Xilinx FPGA.